Marine aquaculture research and development in sub-Saharan African : examples from West, East and Southern Africa [résumé] - (:unkn) unknown (My University, 2022)
World per capita fish consumption is expected to increase by 2030 with the exception of Africa, due to population growth outpacing supply. This raises food and nutrition security issues owing to the high prevalence of malnutrition in the region and the contribution of fish to total animal intake in many African countries. The annual growth rate of Africa's aquaculture production has been the highest worldwide during the last 20 years; however, it represents less than 3% of the world's total annual production. Brackish and freshwater aquaculture production have greatly increased in Africa over the last two decades, while marine aquaculture production has remained low. The latter only represents 5% of the total 2019 production (in tonnes), of which 92% are seaweeds. Marine aquaculture production is very unevenly developed in the different African coastal countries, and Mauritius, South Africa, and Tanzania are by far the main producers of finfish, molluscs, and seaweeds, respectively. The objective of this work is to provide an overview of the current situation of marine aquaculture in several sub-Saharan African countries with different socio-economic and environmental contexts, in which this food production system is at different points of development. The farmed species and/or species of interest that are the subject of research, the new initiatives that are being implemented, as well as the challenges and opportunities to develop marine aquaculture sustainably in Senegal, Ivory Coast, Namibia, South Africa, Mauritius, Tanzania, and Kenya will be presented.
Keywords: African Research